A patient-derived iPSC model revealed oxidative stress increases facioscapulohumeral muscular dystrophy-causative DUX4. (9th August 2018) - Sasaki-Honda, Mitsuru; Jonouchi, Tatsuya; Arai, Meni; Hotta, Akitsu; Mitsuhashi, Satomi; Nishino, Ichizo; Matsuda, Ryoichi; Sakurai, Hidetoshi
Abstract: Double homeobox 4 ( DUX4 ), the causative gene of facioscapulohumeral muscular dystrophy (FSHD), is ectopically expressed in the skeletal muscle cells of FSHD patients because of chromatin relaxation at 4q35. The diminished heterochromatic state at 4q35 is caused by either large genome contractions [FSHD type 1 (FSHD1)] or mutations in genes encoding chromatin regulators, such as SMCHD1 [FSHD type 2 (FSHD2)]. However, the mechanism by which DUX4 expression is regulated remains largely unknown. Here, using a myocyte model developed from patient-derived induced pluripotent stem cells, we determined that DUX4 expression was increased by oxidative stress (OS), a common environmental stress in skeletal muscle, in both FSHD1 and FSHD2 myocytes. We generated FSHD2-derived isogenic control clones with SMCHD1 mutation corrected by clustered regularly interspaced short palindromic repeats (CRISPR)/ CRISPR associated 9 (Cas9) and homologous recombination and found in the myocytes obtained from these clones that DUX4 basal expression and the OS-induced upregulation were markedly suppressed due to an increase in the heterochromatic state at 4q35. We further found that DNA damage response (DDR) was involved in OS-induced DUX4 increase and identified ataxia-telangiectasia mutated, a DDR regulator, as a mediator of this effect. Our results suggest that the relaxed chromatin state in FSHD muscle cells permits aberrant access of OS-induced DDR signaling, thus increasing DUX4 expression. These results suggest OS could represent an environmental risk factor that promotes FSHD progression.